DYNAMIC BEHAVIOUR OF PAPER HONEYCOMB SANDWICH PANELS - Said, M. R. (2012)
Low velocity impact tests have been conducted on paper honeycomb sandwich panels. Two panel thicknesses with span length of 100 mm are used; these are 35 mm and 41 mm, respectively. The dynamic behavior of each paper honeycomb thickness is investigated using two types of indentors: hemispherical and bar. The effect of indentor, and specimen length are studied. This includes the pattern of loaddisplacement curve collapse load and energy absorbed. It concludes that the dynamic collapse load on 41 mm thickness for hemispherical indentor increases by 5% compared with 35 mm. The impact energy absorbed for hemispherical indentor increases by 36%.